Visualization of a Dinoflagellate-Infecting Virus HcDNAV and Its Infection Process - Takano, Yoshihito (Viruses, 2018)
HcDNAV (a type species of Genus Dinodnavirus) is a large double-stranded DNA virus, which lytically infects the bloom-forming marine microalga Heterocapsa circularisquama Horiguchi (Dinophyceae). In the present study, detailed observation of the HcDNAV particle and its infection process was conducted via field emission scanning electron microscopy (FE-SEM) and epifluorescence microscopy (EFM). Each five-fold vertex of the icosahedral virion was decorated with a protrusion, which may be related to the entry process of HcDNAV into the host. The transverse groove of host cells is proposed to be the main virus entry site. A visible DAPI-stained region, which is considered to be the viroplasm (virus factory), appeared in close proximity to the host nucleus at 11 h post infection (hpi); the putative viral DAPI signal was remarkably enlarged at 11–30 hpi. It was kidney-shaped at 13–15 hpi, horseshoe-shaped at 20 hpi, doughnut-shaped at 30 hpi, and changed into a three-dimensionally complicated shape at 51–53 hpi, by which time most parts of the host cell were occupied by the putative viral DAPI signal. While the virions were within the viroplasm, they were easily distinguishable by their vertex protrusions by FE-SEM.